Dust scattering from the Taurus Molecular Cloud. Issue 3 (17th December 2016) - Narayan, Sathya; Murthy, Jayant; Karuppath, Narayanankutty
Abstract: We present an analysis of the diffuse ultraviolet emission near the Taurus Molecular Cloud based on observations made by the Galaxy Evolution Explorer . We used a Monte Carlo dust scattering model to show that about half of the scattered flux originates in the molecular cloud with 25 per cent arising in the foreground and 25 per cent behind the cloud. The best-fitting albedo of the dust grains is 0.3, but the geometry is such that we could not constrain the phase function asymmetry factor ( g ).